2022
DOI: 10.1088/1748-9326/ac60d6
|View full text |Cite
|
Sign up to set email alerts
|

Climate-induced fire regime amplification in Alberta, Canada

Abstract: Acting as a top-down control on fire activity, climate strongly affects wildfire in North American ecosystems through fuel moisture and ignitions. Departures from historical fire regimes due to climate change have significant implications for the structure and composition of boreal forests, as well as fire management and operations. In this research, we characterize the relationship between trends in climate and fire regime characteristics, for a study area predominantly in Alberta, Canada. We examined trends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 89 publications
1
20
0
Order By: Relevance
“…In western North America, trends of increasing homogeneity towards larger and simpler‐shaped patches of stand‐replacing fire have emerged in the Rocky Mountains (Harvey et al, 2016b), south‐west (Miller et al, 2009; Stevens et al, 2017) and north‐west (Cansler & McKenzie, 2014; Reilly et al, 2017). Similar trends of increasing fire extent and severity have been documented in other regions world‐wide (Collins, Bradstock, et al, 2021; Nolan et al, 2020; Pausas & Fernández‐Muñoz, 2012; Whitman et al, 2022). The proportion, mean patch size and patch shape complexity of high‐severity fire characterize important aspects of post‐fire landscapes that underpin mechanisms of resilience, such as the extent and diversity of remnant forest patches (Meddens et al, 2018) and the distance to seed sources required for post‐fire forest recovery (Gill et al, 2022).…”
Section: Introductionsupporting
confidence: 74%
“…In western North America, trends of increasing homogeneity towards larger and simpler‐shaped patches of stand‐replacing fire have emerged in the Rocky Mountains (Harvey et al, 2016b), south‐west (Miller et al, 2009; Stevens et al, 2017) and north‐west (Cansler & McKenzie, 2014; Reilly et al, 2017). Similar trends of increasing fire extent and severity have been documented in other regions world‐wide (Collins, Bradstock, et al, 2021; Nolan et al, 2020; Pausas & Fernández‐Muñoz, 2012; Whitman et al, 2022). The proportion, mean patch size and patch shape complexity of high‐severity fire characterize important aspects of post‐fire landscapes that underpin mechanisms of resilience, such as the extent and diversity of remnant forest patches (Meddens et al, 2018) and the distance to seed sources required for post‐fire forest recovery (Gill et al, 2022).…”
Section: Introductionsupporting
confidence: 74%
“…As in many other ecosystems, fires have dramatic and extensive impacts on vegetation cover and carbon dynamics in the ABZ, and exceptional warming in this region is intensifying fire regimes (Soja et al 2007, Kasischke et al 2010, Veraverbeke et al 2017, McCarty et al 2021, Whitman et al 2022. However, the unique characteristics of ABZ ecosystems result in additional types of disturbances that lack analogs in tropical and temperate ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were also reported in Alaska, with the 2000s showing greater burned areas than the preceding six decades (Kasischke et al 2010). These increases in burned areas were attributed to significantly warmer and drier climate over the later half of the 20th and early 21st centuries in western Canada (Whitman et al 2022) and Alaska (Kelly et al 2013). As warmer and possibly drier climate may well override the capacity to suppress fire (Flannigan et al 2009) it remains uncertain if the observed decrease of burn rates in eastern Canadian boreal forests will continue in the future.…”
Section: Discussionmentioning
confidence: 99%